The impact of sensorimotor training on postural stability and motor skills of basketball players in the prevention of injuries - Wiszomirska, I.; Bender, N.; Patej, M.; Blazkiewicz, M. (Medicina dello Sport, 2017)
BACKGROUND: Little data exists regarding injury risk factors for professional basketball players. Athletes with poor dynamic balance or asymmetrical strength and flexibility are more likely to be injured. The patterns of the Functional Movement Screen (FMS) place the athlete in positions where range of motion, stabilization, and balance deficits may be exposed. The aim of this study was researching the influence of sensorimotor training on postural stability and the progress in motor skills of basketball players. METHODS: The study group comprised of two groups of professional basketball players: group 1 - 18 players that undertook sensorimotor training and group 2 - 10 players that did not undertake sensorimotor training. The tests included: a questionnaire regarding the occurrence of injuries, assessment of postural stability on the unstable platform Biodex Balance System SD and assessment of motor skills via the Functional Movement Screen. RESULTS: All assessments were done twice with an interval of 3 months. The biggest amount of injuries (29%) was to the ankle joint. After 3 months of training on unstable platform, statistically significant progress was noted among the first group. CONCLUSIONS: Results for the Functional Movement Screen showed statistically significant differences in the average result of the tested group that undertook the sensorimotor training.